Poorly differentiated squamous cell carcinoma of the cervix with sarcomatoid differentiation: Report of a case with cytohistological correlation. Issue 2 (27th September 2016) - Akhtar, Israh; Flowers, Rhyne; Nuttli, Theresa; Nath, Vikas; Baliga, Mithra
Abstract : Sarcomatoid squamous cell carcinoma (SSCC) of the uterine cervix is a rare malignancy with uncertain pathogenesis and aggressive clinical behavior. The diagnosis of this tumor poses a challenge to the cytopathologist since accurate diagnosis is based on identification of two malignant components, that is, epithelial and sarcomatoid. Most cases usually lack the sarcomatoid component on Papanicolaou test (Pap test). Therefore, a poorly differentiated carcinoma or malignant neoplasm is the most often rendered diagnosis. To date, less than 20 cases have been reported. Most of these cases were diagnosed by histopathologic findings. To our knowledge, cytomorphologic findings of SSCC on a liquid‐based Pap test, with utility of cell block sections, in recognition of the two components of tumor, with follow‐up histopathologic correlation have not been described. A case of SSCC occurring in a 57‐year‐old postmenopausal woman, describing the cytologic features on a liquid‐based Pap‐test, histopathologic findings of subsequent cervical biopsy, differential diagnosis, and role of ancillary studies are illustrated and discussed. Diagn. Cytopathol. 2017;45:137–142. © 2016 Wiley Periodicals, Inc.